Effect of pre-session discrimination training on performance in a judgement bias test in dogs - Joseph Krahn; Amin Azadian; Camila Cavalli; Julia Miller; Alexandra Protopopova (Animal Cognition)
Abstract Spatial judgement bias tests (JBTs) can involve teaching animals that a bowl provides a reward in one location but does not in another. The animal is then presented with the bowl placed between the rewarded and the unrewarded locations (i.e., ambiguous locations) and their latency to approach reflects expectation of reward or ‘optimism’. Some suggest that greater ‘optimism’ indicates better welfare. Performance in JBTs, however, may also indicate a learning history independently from welfare determinants. We hypothesized that dogs’ ‘optimism’ in a follow-up JBT may be impacted by a learning treatment involving additional trials of a different discrimination task. Once enrolled, companion dogs (n = 16) were required to complete three study phases: (1) a pre-treatment JBT, (2) a learning treatment, and (3) a post-treatment JBT. During the JBTs, dogs were presented with five locations: one rewarded, one unrewarded, and three ambiguous (all unrewarded). Dogs were randomly assigned to a trial-based learning task—a nose-touch to the palm of the hand. In the Experimental discrimination treatment phase (n = 8), dogs were presented with two hands in each trial and only rewarded for touching one specific hand. In the Control treatment phase (n = 8), dogs were presented with one hand per trial in alternating sequence and were yoked to dogs in the Experimental group to receive the same number of rewarded and unrewarded trials (to control for possible frustration). Using a repeated measures mixed model with JBT repeated within dog, we found no difference in the change in approach latency to the ambiguous locations between the dogs across treatments. ‘Optimism’ as measured in this JBT was not altered by the additional discrimination trials used in our study.